Pembelajaran Berbantuan Multimedia untuk Meningkatkan Hasil Belajar Pengetahuan Bagian-bagian Mesin Bubut - Putra, Afiq Junia; Khumaedi, Muhammad; Kriswanto, Kriswanto (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
This study aims to: 1) analyze the feasibility of PowerPoint multimedia on the topic of lathe machine parts; 2) test the effectiveness of PowerPoint multimedia on the topic of lathe machine parts; and 3) analyze the improvement in student learning outcomes after the application of PowerPoint multimedia on the topic of lathe machine parts. The method used in this study is a quantitative approach using the Nonequivalent Control Group Design pattern experimental method. The data collection technique in this study used a test. Post-test data analysis techniques include descriptive analysis, normality test, homogeneity test, right-tailed t-test, and N-Gain test. The results of the validity and reliability tests indicate that the developed multimedia is suitable for use in learning. Based on the results of the t-test, the t-value obtained was 10.013, greater than the t-table of 1.699, indicating a significant difference between the experimental group and the control group. The average post-test score of the experimental class reached 80.00 (78%) with a high category, and the N-Gain analysis showed a greater improvement in learning outcomes compared to the control group.